Хөвсгөл нуурын усны химийн балансын тогтолцоо - Т, Цэнгэл (Scientific transaction of the National University of Mongolia. Physics, 2022)
The purpose of this paper is to determine the chemical balance of Khubsugul lake and its annual variability. The result of study shows that at the depth 0-100 in the lakes mineralization changes from 140-350 mg/l. There had been found negatile linear relationship between mineralization and lake water level during the warm season and there were to clear relation during the winter season when the lake covered by ice. The study shows one interesting results that the mean mineralization mostly depends water level of previous.